2000
DOI: 10.1097/00003072-200012000-00014
|View full text |Cite
|
Sign up to set email alerts
|

SPECT Attenuation Artifacts in Normal and Overweight Persons

Abstract: Attenuation artifacts in TI-201 SPECT occur frequently and are not confined to easily identifiable subgroups of patients. Therefore, measures to improve specificity of SPECT (e.g., prone or gated imaging) or alternative imaging techniques such as PET have potential advantages for everyone, not simply for obese patients and women with large breasts. In addition, awareness of the prevalence of SPECT attenuation artifacts, in both sexes and all weight categories, may contribute to improved accuracy of interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An important confounding factor of myocardial scintigraphy is that 201 Tl myocardial perfusion scintigraphy is subjected to artifacts from the breast and liver [ 19 , 20 ]. As shown in Figure 1 , a thick chest wall or implants in the chest may cause artifacts in SPECT figures of 201 Tl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important confounding factor of myocardial scintigraphy is that 201 Tl myocardial perfusion scintigraphy is subjected to artifacts from the breast and liver [ 19 , 20 ]. As shown in Figure 1 , a thick chest wall or implants in the chest may cause artifacts in SPECT figures of 201 Tl.…”
Section: Discussionmentioning
confidence: 99%
“…As these scores were near the maximum value (full score was 68) of the tests, we regarded them as outliers. These patients were asymptomatic in spite of maximum uptake scores, which suggested that they had some disorders in 123 I-BMIPP uptake, such as CD36 deficiency or triglyceride deposit cardiomyovasculopathy (TGCV) [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer reports regarding the accuracy of myocardial perfusion imaging in severely obese patients. One study [4] using Thallium-201 myocardial perfusion imaging demonstrated lower accuracy in patients with BMI > 30 kg/m 2 , and comparing single photon emission computed tomography (SPECT) results with positron emission tomography (PET), discordance was encountered with greater frequency in obese patients, mostly in the territories supplied by left anterior descending or right coronary arteries, as a result of more prominent attenuation artefacts [22]. In a study by Bhat et al, 7 severely obese patients were evaluated with TE-DSE prior to bariatric surgery to determine cardiac risk.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SPECT imaging is inferior to PET owing to poorer spatial resolution, because resolution is dependent on the distance from the detectors, and the inherent difficulty of performing attenuation correction in SPECT. PET has been shown to have improved specificity in obese patients (84% PET versus 69% SPECT) (30). In practice, PET examinations reduce diagnostic uncertainty compared to SPECT (29, 31).…”
Section: Positron Emission Tomography (Pet) and Coronary Artery DImentioning
confidence: 99%